2018
DOI: 10.1017/s0007114518003045
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of the difference in plasma carotenoid concentrations between men and women

Abstract: Health professionals consider the evaluation of eating habits to be challenging, given the potential biases of dietary questionnaires based on self-reported data. Circulating carotenoid concentrations are reliable biomarkers of dietary carotenoid intake and could be useful in the validation of dietary assessment tools. However, there is a sex difference in circulating carotenoids, with women displaying higher concentrations compared with men independent of intake. The aim of the present study was to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 59 publications
(80 reference statements)
4
28
0
Order By: Relevance
“…β-carotene intake was also similar to the results of a study that was conducted among pregnant Polish women, however the authors reported a lower intake of lycopene and lutein + zeaxanthin [55], although other studies of pregnant women reported a much lower intake of these carotenoids [56,57,58,59]. The NHANES study also showed a much lower lutein intake by women who were at reproductive age [60], although a recent study that was conducted in Canada found a similar intake of lycopene and lutein + zeaxanthin and higher intake of β-carotene [61]. Detailed data on the dietary intake of carotenoids during lactation are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-carotene intake was also similar to the results of a study that was conducted among pregnant Polish women, however the authors reported a lower intake of lycopene and lutein + zeaxanthin [55], although other studies of pregnant women reported a much lower intake of these carotenoids [56,57,58,59]. The NHANES study also showed a much lower lutein intake by women who were at reproductive age [60], although a recent study that was conducted in Canada found a similar intake of lycopene and lutein + zeaxanthin and higher intake of β-carotene [61]. Detailed data on the dietary intake of carotenoids during lactation are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Lutein and zeaxanthin have a higher membrane solubility and a perpendicular orientation within the membrane bilayer which allows them to be more stably bound within the membrane layer compared to carotenes [67]. A recent study comparing dietary and serum carotenoids in men and non-lactating women showed that women have significantly higher concentrations of serum carotenoids than men despite a lower dietary intake of carotenoids, which indicates a sex-difference in the nutritional economy of carotenoids [61].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows the dietary intake of provitamin A carotenoids compiled from the literature [ 16 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Data are listed by geographical origin and by the subpopulations studied in the original articles when reported by age or sex.…”
Section: Resultsmentioning
confidence: 99%
“…A similar pattern was found in the mean values of the compiled studies, 60% β-carotene, 25% β-cryptoxanthin and 15% α-carotene. Although the proportions of β-cryptoxanthin and α-carotene in blood are similar in some studies [ 39 , 45 , 55 ], in others, β-cryptoxanthin concentration is higher than that of α-carotene in blood but not in the dietary intake [ 56 ], or the percentage of blood β-cryptoxanthin is half that of α-carotene [ 48 ] and β-cryptoxanthin is slightly higher than β-carotene [ 37 ]. These differences are clearly seasonal in some population groups [ 8 , 56 ] but could also be due to factors related to the subjects included in the studies since, although in general, no characteristics were reported that could affect carotenoid metabolism, there could be exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are activated by various variables within the body of men and women. The results of one study [ 41 ] showed that the total carotenoid concentration in women’s blood was higher than that in men, even though the dietary carotenoid intake was lower in women, indicating that the absorption and role of carotenoids in the body varies depending on gender. Further research is needed to examine the association between the level of carotenoids in the blood and the physical strength indicators, which have been considered as variables in understanding gender-specific blood indicators and oxidative stress [ 42 ].…”
Section: Discussionmentioning
confidence: 99%